Tolerance of Acacia nilotica to Fluorine Enriched Saline Irrigation Water at Early Growth Stages - Jadoun, B. S.; Singh, Kalyan; Jha, M. N. (Indian Forester, 2000)
A field trial of Acacia nilotica (Linn) Willd. ex Delile was conducted in polythene lined micro-plots to evaluate its tolerance to fluorine enriched saline irrigation water at early growth stages, using varying qualities of artificially prepared saline water (2.5, 5, 7.5, 10, 20 ppm Fluorine levels maintained at EC 4 and 8 dS/m) for irrigation on sandy loam soil (Coarse-loamy mixed hyperthermic Ustorthent). The best available canal water having EC 0.2 dS/m (Fluorine traces) was used as control. Acacia nilotica grew well with retarded growth at 20 ppm fluorine levels. However, the 50% reduction in biomass yield of Acacia nilotica as limits of tolerance was observed at about 20 and 18 ppm fluorine levels in saline water of 4 and 8 dS/m, respectively. Uptake of fluorine by plants increased progressively with increase in fluorine levels. Subsequently the uptake the Na+ increased but phosphorus and Ca2+ decreased. Nitrogen, K+ and Mg2+ uptake did not show any particular trend.